Factors Influencing the Success of Experiential Learning Model in Solonese Bridal Makeup Course - Ihsani, Ade Novi Nurul; Maghfiroh, Anik; Suyitno, Suyitno; Mahfud, Tuatul; Chana, Kieng; Azzahra, Nadhifa (Universitas Ahmad Dahlan, 2025)
The learning process can run well if it supported by the components that exist in learning. Components in learning cannot stand alone, they are interrelated with one another because learning is a system. The components of the learning process include students, objectives, media, learning strategies, etc. In experiential learning, there are several indicators that need to be examined, especially in learning Solo bridal make-up in the Beauty Study Program, namely direct experience, environmental support, learning media and learning activities on the successful implementation of experiential learning on Solo bridal make-up material. This study aims to: disclose the influence of learning media, direct experience, environmental support, and learning activities on the developed learning model. The type of study conducted is ex post facto. Product validation was carried out by vocational education experts, learning media experts, and bridal make-up artist. In order to obtain expert consensus on the developed instrument validity, FGD session was carried out. The next stage was to conduct an experiment involving 32 students from the Cosmetology Study Program. Data analysis was conducted to see the influence of learning media, direct experience, environmental support, and learning activities on the learning model using SEM-AMOS. The results of the study using SEM indicated that learning media, direct experience, environmental support, and learning activities can influence the success of experiential learning of Solonese bridal makeup.